KEBIJAKAN PENDIDIKAN DI AMERIKA SERIKAT - Taat Wulandari (Universitas Negeri Yogyakarta, 2008)
AbstractRegarding education is a means of countries to develop, there are some policiesand strategies to fulfill the above mission. Such as to provide good infrastructures andstructures to develop curriculum, to develop the quality of teachers, to increase education budget and to adopt the good aspect of others education system.This article is to elaborate education system in United States of America. Despite there are some countries which have good education system, USA has relatively good education system. It is not surprisingly that there are some qualified universities, so that some students choose these universities for studying. Up to now the numbers of Indonesian graduate from USA is still in the first range.Keywords: Education, policy.